Ecophysiology and morphology of seed germination and seedling emergence of Combretum lanceolatum Pohl ex Eichler - Soares, Vanessa Couto; de Vargas, Wanderleia; de Menezes Zanoni, Ana Maria; Daibes, L. Felipe [UNESP]; de Lima, Liana Baptista (My University, 2021)
Combretum lanceolatum Pohl ex Eichler is a widely dominant species of the Pantanal wetland, Brazil. We investigated the ecophysiological and morphological features of seed germination and seedling emergence to explain the establishment success of C. lanceolatum in the field. Hence, seed morphoanatomy and seedling morphology were described. Germination tests were conducted in different substrate types (filter paper and rolled paper towel), temperatures, and light regimes. Normal seedling emergence was also observed in different temperatures by sowing whole fruit in rolled paper towel and seed upon filter paper. Seedling emergence and early growth were evaluated using four substrates under greenhouse conditions: commercial substrate, red soil + sand, sand + vermiculite, and coconut fiber. Overall, C. lanceolatum seed is exalbuminous, showing a narrow ellipsoid tetragonal shape. The embryo is axile type, foliate folded and anatomically bitegmic cotyledons, whose cells display prismatic crystals, phenolic compounds, and store starch. Germination type is cryptocotylar hypogeal. Germination capacity is high (mostly > 80%) irrespective of substrate type, temperature, and light regime, which affected germination speed/time. Despite the broad germination range, normal seedling emergence occurred in fewer temperatures. Whole fruit imposed no impediment for germination producing up to 67% of normal seedlings. Commercial substrate provided the best conditions for seedling emergence/growth under greenhouse conditions. C. lanceolatum seed shows no dormancy, promptly emergenced in a wide range of experimental factors, while its hypogeal seedling protects the cotyledons and contributes to its establishment and wide dominance in the Pantanal wetland. Our results provide ecologically relevant information on regeneration from seed and practical applications for plant propagation to aid restoration initiatives in tropical wetlands.
Keywords: Combretaceae; Early growth; Monodominant; Pantanal wetland; Seed anatomy; Temperature